Metaphor of Seloko Adat in Merangin - Magria, Vera; Afrilesa, Rini (Fakultas Sastra Universitas Ekasakti, 2024)
This research clarifies about the kinds of methapors that found in the” seloko Adat” traditional ceremonies in merangin culture This research applied descriptive qualitative research in which the data are obtained from seloko adat in traditional ceremony. it took from Lubuk Bumbun village in Merangin regency. The data are collected by observational method supported by note-taking and interview technique. After analyzing the data, it is found that there are 10 metaphors included into three from four kinds of methapor. The result of the research showed there are animistic, synaesthetic and concret to abstreact of methapor. Animistic metaphor dominant exist in seloko adat traditional ceremonies on Merangin culture .The meaning of each metaphor is understood in light of the current situation.